Ελληνικά ρωμαντικά χρόνια : άνθρωποι, ιδέες, ζωή - Αγγελομάτης, Χρήστος, 1904-1979
Σούτσος, Αλέξανδρος -- Σούτσος, Παναγιώτης -- Ραγκαβής, Αλέξανδρος -- Ιακωβάκης, Ρίζος Νερουλός -- Παράσχος, Αχιλλεύς -- Ορφανίδης, Θεόδωρος -- Ζαλοκώστας, Γεώργιος -- Παράσχος, Γεώργιος